Studying Lipid-Related Pathophysiology Using the Yeast Model - Ralph-Epps, Tyler; Onu, Chisom J.; Vo, Linh; Schmidtke, Michael W.; Le, Anh; Greenberg, Miriam L. (Frontiers in Physiology, 2021)
Saccharomyces cerevisiae, commonly known as baker’s yeast, is one of the most comprehensively studied model organisms in science. Yeast has been used to study a wide variety of human diseases, and the yeast model system has proved to be an especially amenable tool for the study of lipids and lipid-related pathophysiologies, a topic that has gained considerable attention in recent years. This review focuses on how yeast has contributed to our understanding of the mitochondrial phospholipid cardiolipin and its role in Barth syndrome, a genetic disorder characterized by partial or complete loss of function of the cardiolipin remodeling enzyme tafazzin. Defective tafazzin causes perturbation of cardiolipin metabolism, resulting in many downstream cellular consequences and clinical pathologies that are discussed herein. The influence of yeast research in the lipid-related pathophysiologies of Alzheimer’s and Parkinson’s diseases is also summarized.